Understanding multiscale structure–property correlations in PVDF-HFP electrospun fiber membranes by SAXS and WAXS. Issue 2 (7th December 2021) - Maurya, Anjani K.; Mias, Eloïse; Schoeller, Jean; Collings, Ines E.; Rossi, René M.; Dommann, Alex; Neels, Antonia
Abstract : Multiscale structure–property correlations in PVDF-HFP electrospun fiber membranes. Abstract : Electrospinning is a versatile technique to produce nanofibrous membranes with applications in filtration, biosensing, biomedical and tissue engineering. The structural and therefore physical properties of electrospun fibers can be finely tuned by changing the electrospinning parameters. The large parameter window makes it challenging to optimize the properties of fibers for a specific application. Therefore, a fundamental understanding of the multiscale structure of fibers and its correlation with their macroscopic behaviors is required for the design and production of systems with dedicated applications. In this study, we demonstrate that the properties of poly(vinylidene fluoride- co -hexafluoro propylene) (PVDF-HFP) electrospun fibers can be tuned by changing the rotating drum speed used as a collector during electrospinning. Indeed, with the help of multiscale characterization techniques such as scanning electron microscopy (SEM), small-angle X-ray scattering (SAXS), and wide-angle X-ray scattering (WAXS), we observe that increasing the rotating drum speed not only aligns the fibers but also induces polymeric chain rearrangements at the molecular scale. Such changes result in enhanced mechanical properties and an increase of the piezoelectric β-phase of the PVDF-HFP fiber membranes. We detect nanostructural deformation behaviors when the aligned fibrous membrane is uniaxially stretched along the fiber alignment direction, while an increase in the alignment of the fibers is observed for randomly aligned samples. This was analyzed by performing in situ SAXS measurements coupled with uniaxial tensile loading of the fibrous membranes along the fiber alignment direction. The present study shows that fibrous membranes can be produced with varying degrees of fiber orientation, piezoelectric β-phase content, and mechanical properties by controlling the speed of the rotating drum collector during the fiber production. Such aligned fiber membranes have potential applications for neural or musculoskeletal tissue engineering.